Parental experience and use of probiotics among children aged twelve months and above - Atif Amin, Baig; Muhammad Kashif, Munir; Samina, Khaliq (2019)
Probiotics are the food products containing live microorganisms which when up-taken in sufficient quantities, converse health benefits to consumers. This study was aimed to find parental awareness, level of utilization, assessment of their experiences and sentiments about probiotics among their children. This descriptive study was undertaken in King Edward Medical University Lahore during July 2017 to January 2018. A total of 127 questionnaires were successfully completed comprising 45 (35.5%) from health care staff, 52 (40.9%) from parents visiting pediatric outpatients and 30 (23.6%) from school teachers. Maternal parent remained predominant in this study as there were 109 (85.8%) female and 18(14.2%) male respondents. Only 20(15.7%) were familiar with the term probiotics, 49 (38.6%) were somewhat familiar while 58 (45.6%) had no idea about term. On pursuing about preferences regarding probiotics use majority 106/127 (83.5%) of parents like to available in liquid as it is easy to consume for children. Use of probiotics among children is not very much common however it is been prescribed for number of gastrointestinal problems. Only a limited class of people is familiar with health benefits probiotics. Around 20% users do not know about the organism present in specific probiotic is also of astonishing. Due to different social set up health care providers and family physicians must discuss about the dietary supplements in terms of potential risks and benefits.